Disability and its association with sociodemographic factors among elderly persons residing in an urban resettlement colony, New Delhi, India. - Anil Kumar Goswami; Ramadass S; Mani Kalaivani; Baridalyne Nongkynrih; Shashi Kant; Sanjeev Kumar Gupta (PLoS ONE, 2019)
Disability prevents an individual from performing to the fullest potential. It is multidimensional. Disability may be physical, mental, social, personal, and environmental or a combination of these. The elderly experience an increased burden of disability, especially in areas where there are limited resources and rapid urbanization. Comparison of reported disability is difficult because several definitions and scales are in use. We used the World Health Organization Disability Assessment Schedule version 2.0 (WHODAS 2.0) to study the prevalence of disability, and its association with sociodemographic factors among elderly persons residing in an urban resettlement colony, New Delhi, India. The WHODAS 2.0 provides continuous summary scores, where higher scores indicate higher disability, and vice versa. Elderly persons aged 60 years and above were selected by simple random sampling in this community-based cross-sectional study. Trained interviewers administered the semi-structured interview schedule and WHODAS 2.0. The prevalence of disability was 7.4% (5.8% - 9.3%) among the 931 participants. The prevalence was higher among females than males. Female sex, elderly aged 70 years and above, and those who were illiterate had increased risk of higher disability scores. Participants who were in government or private service had 50% decreased risk of having higher disability scores. The burden of disability was high among elderly persons residing in this resettlement colony. Community-based holistic interventions are required to mitigate the disability, and to improve the functioning of elderly persons.